The role of nurses in improving self-care for diabetes mellitus patients in primary care: A cross-sectional study - Aulia, Siti; Rizky, Virza (Science Center Group, 2025)
Background: Diabetes mellitus represents a major global health challenge requiring continuous self-care management to prevent long-term complications. Primary health care services play a crucial role in supporting patient self-management through structured education and behavioral guidance. Nurses working in community health centers (Puskesmas) function as key facilitators in empowering patients to perform independent self-care practices. Objective: To analyze the role of nurses in improving self-care behaviors among patients with diabetes mellitus within the Puskesmas service area. Methods: A quantitative descriptive-analytic study with a cross-sectional design was conducted among patients with type 2 diabetes mellitus receiving treatment at a Puskesmas. Participants were selected using a consecutive sampling technique based on predefined inclusion criteria. Data were collected using two validated instruments: a nurse role questionnaire assessing educational, motivational, and facilitative roles, and the Summary of Diabetes Self-Care Activities (SDSCA) questionnaire measuring dietary management, physical activity, blood glucose monitoring, and foot care. Data were analyzed using descriptive statistics and bivariate analysis with the Chi-square test to determine associations between nursing roles and patient self-care behavior. Results: Most respondents perceived nurses’ roles positively, particularly in educational and motivational domains. The overall level of patient self-care was categorized as moderate, with the highest adherence observed in dietary management practices. Lower adherence was found in physical activity and foot care domains. Statistical analysis demonstrated a significant relationship between the active role of nurses and improved patient self-care behavior. Patients receiving comprehensive nursing education and motivational support were more likely to demonstrate regular blood glucose monitoring and consistent disease management practices. Conclusion: The role of nurses as educators and motivators contributes significantly to improving self-care independence among patients with diabetes mellitus at the primary health care level. Strengthening structured nursing interventions in community health services may enhance patient empowerment and reduce the risk of diabetes-related complications.